A History of the World in Sixteen Shipwrecks - Gordon, Stewart, 1945- (Book collections on Project MUSE., 2015)
"An examination of 16 shipwrecks from ancient to modern times, and what they show about culture, trade, technology, and the movement of peoples"--Provided by publisher.